2010
DOI: 10.1111/j.1365-2141.2010.08109.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels in sickle‐cell disease associated with haemolytic severity, vascular dysfunction and pulmonary hypertension

Abstract: Pulmonary hypertension (PH) in sickle cell disease (SCD) is an emerging and important clinical problem. In a single-institution adult cohort of 365 patients, we investigated lipid and lipoprotein levels and their relationship to markers of intravascular hemolysis, vascular dysfunction and PH. In agreement with prior studies, we confirm significantly decreased plasma levels of total cholesterol, high-density lipoprotein-cholesterol (HDL-C), and low-density lipoprotein-cholesterol (LDL-C) in SCD vs. ethnically-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 51 publications
10
109
3
Order By: Relevance
“…Hypocholesterolemia is the most frequently reported lipid abnormality besides decreased lipoprotein and increased triglyceride levels in the sickle plasma [16]. However, the pathophysiology of these abnormalities is obscure.…”
Section: Discussionmentioning
confidence: 96%
“…Hypocholesterolemia is the most frequently reported lipid abnormality besides decreased lipoprotein and increased triglyceride levels in the sickle plasma [16]. However, the pathophysiology of these abnormalities is obscure.…”
Section: Discussionmentioning
confidence: 96%
“…Despite intense research for over 4 decades, mechanism of lipid homeostasis alteration in SCA subjects is not yet fully understood 11. The observed lower levels of TC, HDL and LDL in the combined SCA subjects (SSCA and VOC) are not novel findings.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is worthy of note that this lipid phenotype is generally recognized as a risk factor for cardiovascular diseases. Zorca et al 11. reported that elevated plasma TG is a potential risk factor for pulmonary hypertension (PH) in SCA subjects.…”
Section: Introductionmentioning
confidence: 99%
“…This is also correct. Published data evidence the involvement of oxidative stress (79,100,105,108,113,115,116,121,123,132,134,135), inflammation (9, 22, 27, 32, 101, 105-108, 115, 124-127, 134), dyslipidemia (135)(136)(137)(138), microparticles (89,122,123,139), and vasoactive peptides (110,111,(140)(141)(142)(143). These additional pathways (depicted in Figure 2) are potentially additive or synergistic to intravascular hemolysis-like mechanisms.…”
Section: Controversies Regarding the Hyperhemolysis Modelmentioning
confidence: 99%